3(2r+5)-4(r-9)=

Simple and best practice solution for 3(2r+5)-4(r-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2r+5)-4(r-9)= equation:


Simplifying
3(2r + 5) + -4(r + -9) = 0

Reorder the terms:
3(5 + 2r) + -4(r + -9) = 0
(5 * 3 + 2r * 3) + -4(r + -9) = 0
(15 + 6r) + -4(r + -9) = 0

Reorder the terms:
15 + 6r + -4(-9 + r) = 0
15 + 6r + (-9 * -4 + r * -4) = 0
15 + 6r + (36 + -4r) = 0

Reorder the terms:
15 + 36 + 6r + -4r = 0

Combine like terms: 15 + 36 = 51
51 + 6r + -4r = 0

Combine like terms: 6r + -4r = 2r
51 + 2r = 0

Solving
51 + 2r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-51' to each side of the equation.
51 + -51 + 2r = 0 + -51

Combine like terms: 51 + -51 = 0
0 + 2r = 0 + -51
2r = 0 + -51

Combine like terms: 0 + -51 = -51
2r = -51

Divide each side by '2'.
r = -25.5

Simplifying
r = -25.5

See similar equations:

| -2(1+x)=7-5x | | b-4=-19 | | -7(-6b-5)=35-5b | | 6(2x-10)=0 | | 14+3d-7=12.10 | | -5(x+6)=5x-20 | | -(8+x)=-8+7x | | -18=18v | | 14x^2+10x-8=0 | | 2(t-4)-3(4t-5)=10-5(7t+3) | | 32+4m=-3(-5m-2)+2m | | -3(n-5)=15+4n | | 6x-2=3x-10 | | 4(1/4+x)=5 | | 7z-4=7z-z | | 6(1+7n)=40+8n | | 2x^2+9x=35 | | -4x^2(5x^2-21x-y)= | | 3(x-1)=-7(x-1) | | 1-5m=6(1-m) | | 7(3x+2)+22=36 | | -0.04x+1.32=1.08 | | 4(6x+5)=2+6x | | -3(4-y)=27 | | -1(3w-4)+12w=3w+4 | | 3m-5=5m+2 | | -27-3k=-6(k+2) | | X+20=6x+5 | | 6-3(2k-4)=-18 | | -3(4-y)=-2 | | r-3.8=9.4 | | -6a+2a=-36 |

Equations solver categories